SOME THEORETICAL ISSUES IN THE DEVELOPMENT OF LAW IN THE COUNTRIES OF CENTRAL ASIA IN THE CONTEXT OF DIGITALIZATION (TSUL LEGAL REPORT, 2026)
The article analyzes and compares the legal developments of the countries of Central Asia in the context of digitalization of all aspects of public life, including the legal sphere. There is a commonality in the legal development, due to the commonality of their historical development, religion, culture, customs, mentality of these countries. Also, the region in which they are located is the basis for uniting them into a separate group.The author tried to analyze the common features of the legal systems of these countries, as well as those features that are inherent in the legal development of individual countries of this region. It is noted that the judicial system of these countries is developing along the same vector towards the creation of a truly independent judicial system, which does not exclude the presence of certain aspects in development, in particular the institution of jury trial in Kazakhstan, attempts to create such in Kyrgyzstan, etc. or those common and distinctive features that took place in the systems of sources of law in these countries regarding the status of decisions of the Supreme Courts. The article also notes those trends in the legal development of these countries, such as the influence of English law and its application in the field of international cooperation, more precisely in the field of business and commerce.